Wave-absorbing basalt fiber with cobalt-zinc bimetallic organic framework grown in situ on surface, preparation method and application thereof
Patent Information
- Application Number
- CN202611158398.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
传统吸波涂层通常以铁氧体、磁性金属微粉等为吸收剂,普遍存在密度大、频带窄、厚度厚以及维护成本高等不足,难以满足新一代装备对轻量化、宽频带及多功能化的严苛要求
本发明基于“酸刻蚀-硅烷锚定-原位水热生长-碳化”的界面工程策略,在玄武岩纤维表面构筑Co-Zn双金属ZIF衍生碳异质吸波界面。首先,通过酸刻蚀处理对惰性玄武岩纤维表面进行活化,在不破坏纤维本体结构的前提下增加表面粗糙度并暴露活性羟基位点,为后续界面改性提供反应基础。随后,利用KH550硅烷偶联剂对活化纤维进行桥接改性,通过硅烷水解缩合引入氨基锚定位点,提高其对金属离子的吸附能力,促进Co²+和Zn²+富集,并诱导Co-Zn双金属ZIF晶体原位成核与生长,构筑纤维界面的异质结构。经碳化处理,双金属ZIF转化形成碳基功能层,同时进一步增强与玄武岩纤维之间的界面稳定性。上述界面构筑策略实现了Co-Zn双金属ZIF衍生碳功能层在玄武岩纤维上的稳定构筑,为后续调控材料结构及性能优化提供了基础。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic wave absorbing materials and high-performance fiber modification technology, specifically to a microwave absorbing basalt fiber with cobalt-zinc bimetallic zeolite imidazole ester (ZIF)-derived carbon grown in situ on the surface, its preparation method, and its application in the field of electromagnetic protection. Background Technology
[0002] With the large-scale application of 5G mobile communication technology and the high integration of electronic devices, electromagnetic interference and radiation problems are becoming increasingly serious. Developing high-performance electromagnetic wave absorbing materials is one of the key ways to solve electromagnetic pollution and ensure information security and human health. Basalt fiber (BF), as one of the four key high-performance fibers under development, possesses comprehensive advantages such as lightweight and high strength, resistance to high and low temperatures, resistance to chemical corrosion, and excellent dielectric properties, making it an ideal substrate for preparing electromagnetic protection materials resistant to extreme environments. However, basalt fiber is intrinsically insulating, has a smooth surface, and is chemically inert, lacking inherent electromagnetic wave loss capabilities. Furthermore, traditional methods such as physical coating and chemical plating generally suffer from weak interfacial bonding, demanding preparation conditions (requiring high temperature and pressure or strong corrosive reagents), and easy damage to the fiber's structure, severely restricting the high-value application of basalt fiber in the field of electromagnetic protection.
[0003] Furthermore, in the military field, radar stealth technology is crucial to the survivability and penetration effectiveness of weapon platforms. Traditional radar-absorbing coatings typically use ferrites, magnetic metal powders, etc., as absorbers, and generally suffer from drawbacks such as high density, narrow bandwidth, thick thickness, and high maintenance costs, making it difficult to meet the stringent requirements of next-generation equipment for lightweight, wide bandwidth, and multi-functionality. Therefore, developing fiber-based radar-absorbing materials that combine lightweight, wide bandwidth absorption, and excellent environmental adaptability is of significant strategic importance in reducing the radar cross section (RCS) of military equipment and improving battlefield survivability.
[0004] Metal-organic frameworks (MOFs) and their derivatives have shown great potential in the field of electromagnetic wave absorption in recent years due to their high specific surface area, tunable pore structure, and abundant metal active sites. Among them, zeolite imidazole ester frameworks (ZIFs) combine the advantages of high stability similar to zeolites with mild synthesis conditions. However, how to achieve in-situ dense growth and uniform anchoring of ZIF crystals on the surface of inert basalt fibers, and maintain their strong bond with the fibers after high-temperature carbonization, remains an unsolved technical challenge in this field.
[0005] Therefore, there is an urgent need to develop a method that can gently and controllably construct an efficient electromagnetic wave loss interface on the surface of basalt fibers without damaging the bulk structure of the basalt fibers, thereby directly endowing the basalt fibers with excellent wave absorption capabilities. Summary of the Invention
[0006] The purpose of this invention is to provide a microwave absorbing basalt fiber with a cobalt-zinc bimetallic organic framework grown in situ on the surface, as well as its preparation method and application, in order to solve the problems existing in the prior art. Through interface engineering strategy, this invention achieves for the first time the in-situ growth and subsequent carbonization of cobalt-zinc bimetallic ZIF on the surface of inert basalt fiber, successfully constructing a magnetic porous microwave absorbing interface, enabling basalt fiber to be directly transformed from a wave-transmitting body into a highly efficient electromagnetic wave absorber.
[0007] This invention is achieved through the following technical solution: A method for preparing microwave-absorbing basalt fibers with cobalt-zinc bimetallic organic frameworks grown in situ on the surface includes the following steps: S1. Basalt fiber pretreatment: Basalt fibers are immersed in nitric acid etching solution to perform surface roughening etching treatment, thereby obtaining activated basalt fibers. S2. Fiber surface silanization modification: The activated basalt fiber obtained in S1 is immersed in a solution containing KH550 silane coupling agent to carry out silanization grafting modification to obtain amino-functionalized basalt fiber. S3. In-situ growth of Co-Zn bimetallic organic framework: Cobalt and zinc salts are dissolved in deionized water to prepare a mixed metal salt solution. 2-Methylimidazole is dissolved in deionized water to form a ligand solution. The mixed metal salt solution is added to the ligand solution and stirred to obtain a mixed solution. The amino-functionalized basalt fibers obtained in S2 are immersed in the mixed solution and subjected to a hydrothermal synthesis reaction. After filtration and washing, the product is subjected to carbonization treatment to obtain microwave absorbing basalt fibers with in-situ grown cobalt-zinc bimetallic organic framework.
[0008] Furthermore, the surface roughening etching process in S1 is carried out at a temperature of 40~60℃ for a time of 4~6h.
[0009] Furthermore, the silanization grafting modification treatment time in S2 is 6~12h, and the treatment temperature is 25℃~60℃.
[0010] Furthermore, the molar ratio of cobalt metal to zinc metal in S3 is 1:2 to 3:1.
[0011] Furthermore, the molar ratio of 2-methylimidazole to the total amount of cobalt and zinc metals in S3 is 6:1 to 12:1.
[0012] Furthermore, the hydrothermal synthesis reaction in S3 is carried out at a temperature of 45~80℃ for 6~12h.
[0013] Furthermore, the carbonization treatment in S3 specifically involves heating to 700°C at a rate of 5~10°C / min and then holding the temperature for 0.5~2 hours.
[0014] A microwave-absorbing basalt fiber with a cobalt-zinc bimetallic organic framework grown in situ on the surface was prepared using the above-described preparation method.
[0015] Furthermore, the minimum reflection loss of the absorbing basalt fiber with the cobalt-zinc bimetallic organic framework grown in situ on the surface is -7.02 dB to -53.07 dB, and the effective absorption bandwidth is 0 to 6.88 GHz.
[0016] Application of absorbing basalt fibers with in-situ grown cobalt-zinc bimetallic organic frameworks as electromagnetic wave absorbers in resin-based, coating-based, or paper-based composite materials.
[0017] Compared with the prior art, the present invention has the following beneficial technical effects: This invention utilizes an interface engineering strategy of "acid etching-silane anchoring-in-situ hydrothermal growth-carbonization" to construct a Co-Zn bimetallic ZIF-derived carbon heterogeneous microwave absorbing interface on the surface of basalt fibers. First, the surface of inert basalt fibers is activated by acid etching, increasing surface roughness and exposing active hydroxyl sites without damaging the fiber's bulk structure, providing a reaction basis for subsequent interface modification. Then, the activated fibers are bridged using KH550 silane coupling agent, introducing amino anchoring sites through silane hydrolysis and condensation, enhancing their adsorption capacity for metal ions and promoting Co²⁺ adsorption. + and Zn² + Enrichment and induction of in-situ nucleation and growth of Co-Zn bimetallic ZIF crystals were achieved, constructing a heterogeneous structure at the fiber interface. Following carbonization, the bimetallic ZIF was transformed into a carbon-based functional layer, further enhancing the interfacial stability with the basalt fibers. This interface construction strategy achieved the stable construction of the Co-Zn bimetallic ZIF-derived carbon functional layer on basalt fibers, providing a foundation for subsequent control of material structure and performance optimization.
[0018] This invention achieves a controllable evolution of the microstructure of ZIF-derived carbon on the fiber surface from needle-like to petal-like and then to fine granular, by precisely controlling the molar ratio of cobalt-zinc metal salts. This allows for effective control of the fiber's electromagnetic parameters and microwave absorption performance. When the cobalt-zinc molar ratio is 3:1, the resulting microwave absorbing fiber achieves an effective absorption bandwidth of 6.88 GHz (fully covering the Ku band) at a thickness of 2.5 mm, and a minimum reflection loss as low as -53.07 dB at a thickness of 2.7 mm, exhibiting excellent electromagnetic wave absorption performance.
[0019] The absorbing basalt fiber prepared by this invention can not only be used directly as an electromagnetic wave absorber, but also as a widely applicable material for paper-based electromagnetic shielding materials and photothermal conversion materials. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. The following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 Scanning electron microscope (SEM) images of the surface morphology of basalt fibers at different stages; where a is the original basalt fiber, b is the fiber surface after nitric acid etching in Example 1, and c is the fiber surface after silane coupling agent treatment in Example 1.
[0022] Figure 2 SEM images of the surface morphology of microwave-absorbing basalt fibers prepared under different cobalt-zinc molar ratios; where a1-a3 are Example 1 (Co / Zn=1:1), b1-b3 are Example 2 (Co / Zn=1:2), c1-c3 are Example 3 (Co / Zn=2:1), and d1-d3 are Example 4 (Co / Zn=3:1).
[0023] Figure 3 This is an EDS surface scan of the elemental distribution of microwave-absorbing basalt fibers with a cobalt-zinc bimetallic organic framework grown in situ on the surface.
[0024] Figure 4 The reflection loss (RL) curves of microwave absorbing basalt fibers (mixed with paraffin at a filling amount of 40 wt%) prepared under different cobalt-zinc molar ratios were measured by the coaxial method; where a is Example 1 (Co / Zn=1:1), b is Example 2 (Co / Zn=1:2), c is Example 3 (Co / Zn=2:1), and d is Example 4 (Co / Zn=3:1).
[0025] Figure 5 The image shows a comparison of the simulated radar cross section (RCS) curves of a perfectly conductive (PEC) plate before and after coating with the absorbing fiber prepared in Example 4, with the incident angle ranging from -90° to 90°.
[0026] Figure 6 SEM images of the surface morphology of microwave-absorbing basalt fibers obtained at different etching times; where a is Comparative Example 1 (etched for 2 hours), b is Example 1 (etched for 4 hours), and c is Comparative Example 2 (etched for 8 hours).
[0027] Figure 7 SEM images of the surface morphology of the microwave-absorbing basalt fibers prepared by omitting the silanization step in Comparative Example 3. Detailed Implementation
[0028] The present invention will now be described in detail: A method for preparing microwave-absorbing basalt fibers with cobalt-zinc bimetallic organic frameworks grown in situ on the surface includes the following steps: (1) Basalt fiber pretreatment: Basalt fibers are immersed in nitric acid etching solution to perform surface roughening etching treatment to obtain activated basalt fibers; wherein, the surface roughening etching treatment temperature is 40~60℃ and the time is 4~6h; (2) Silanization bridging modification: The activated fiber obtained in step (1) is immersed in the hydrolysis solution of KH550 silane coupling agent, and active amino anchoring sites are introduced on the fiber surface through silanization reaction (i.e. silanization grafting modification) to obtain amino-functionalized basalt fiber; wherein the silanization treatment time is 6~12h and the treatment temperature is 25℃~60℃.
[0029] (3) In-situ growth of cobalt-zinc bimetallic ZIF: Cobalt salt and zinc salt are dissolved in deionized water to prepare a mixed metal salt solution, and then a ligand solution (using 2-methylimidazole as a ligand, dissolved in deionized water to form a ligand solution) is added and stirred. The amino-functionalized basalt fiber obtained in step (2) is immersed in the mixed solution and then subjected to a hydrothermal synthesis reaction. After filtration and washing, it is subjected to high-temperature carbonization treatment to obtain microwave absorbing basalt fiber with cobalt-zinc bimetallic organic framework derived carbon on the surface. The molar ratio of cobalt metal to zinc metal is 1:2 to 3:1; the molar ratio of ligand to total metal salt is 6:1 to 12:1; the hydrothermal synthesis reaction temperature is 45 to 80°C, and the reaction time is 6 to 12 hours; the carbonization treatment is carried out at a rate of 5 to 10°C / min to 700°C, followed by a further heat treatment for 0.5 to 2 hours.
[0030] This invention also provides microwave absorbing basalt fibers with in-situ grown cobalt-zinc bimetallic organic frameworks prepared by the above-described method. The minimum reflection loss of the microwave absorbing basalt fibers is -7.02 dB to -53.07 dB, and the effective absorption bandwidth can reach up to 6.88 GHz.
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise specified, the methods and experimental equipment used in the following embodiments are conventional methods and instruments.
[0032] Example 1 The microwave-absorbing basalt fiber with cobalt-zinc bimetallic organic framework grown in situ on the surface of this embodiment and its preparation method specifically include the following steps: (1) Basalt fiber pretreatment: Basalt fiber was placed in nitric acid aqueous solution (H2O:HNO3 volume ratio 2:1), etched at 60℃ for 4 h, washed with deionized water until neutral, and dried to obtain activated basalt fiber; (2) Silanization bridging modification: Prepare an ethanol / water (volume ratio 9:1) mixed solvent, add 1 wt% silane coupling agent KH-550 and stir evenly. Immerse the activated fiber obtained in step (1) into the solution, react at 60℃ for 12h, take it out and wash it thoroughly with deionized water and dry it to obtain amino-functionalized basalt fiber; (3) In-situ growth of cobalt-zinc bimetallic ZIF: Co(NO3)2·6H2O and Zn(NO3)2·6H2O were weighed according to the Co / Zn molar ratio of 1:1 and dissolved in deionized water to obtain a mixed metal salt solution; 2-methylimidazolium was dissolved in deionized water as a ligand solution, and the ratio of ligand to total metal salt was 8:1. The mixed metal salt solution was quickly poured into the ligand solution and stirred at room temperature for 10 min. Then, the amino-functionalized fiber obtained in step (2) was added, and the product was hydrothermally reacted at 65℃ for 6 h. The product was repeatedly washed with deionized water, dried, and then carbonized in a tube furnace. The temperature was increased to 700℃ at 5℃ / min under a nitrogen atmosphere and held for 2 h to obtain microwave absorbing basalt fiber.
[0033] (4) The surface morphology of the fiber obtained in this embodiment is as follows: Figure 1 As shown. Among them, Figure 1 In the middle a, the original basalt fiber has a smooth and flat surface and lacks active anchoring points; Figure 1 In Figure b, the fiber surface is etched at 60°C for 4 hours with nitric acid. It is evident that the surface is significantly roughened and uniform etch grooves are generated, which is beneficial for the subsequent chemical bonding of the silane coupling agent. Figure 1 In the middle, c represents the fiber surface after being treated with KH-550 at 60℃ for 12 hours. The surface is covered with a uniform organic film, and the overall morphology is restored to a smooth state.
[0034] (5) Figure 2 Tables a1-a3 show the SEM morphology of the fiber surface obtained in this embodiment. It can be seen that the ZIF-derived carbon is arranged in a dense, needle-like pattern on the fiber surface, with uniform and complete coating. The surface morphology was determined by EDS surface scanning (…). Figure 3 This further confirms that Co and Zn elements are uniformly distributed on the fiber surface without obvious segregation, proving that the ZIF-derived carbon layer has been successfully and uniformly coated on the fiber surface.
[0035] (6) Absorption performance test, such as Figure 4 As shown in Figure a, the minimum reflection loss at a thickness of 6.7 mm is -30.29 dB, and the effective absorption bandwidth is 4.88 GHz.
[0036] Example 2 The microwave-absorbing basalt fiber with cobalt-zinc bimetallic organic framework grown in situ on the surface of this embodiment and its preparation method specifically include the following steps: (1) Basalt fiber pretreatment: Basalt fiber was placed in nitric acid aqueous solution (H2O:HNO3 volume ratio 2:1), etched at 40℃ for 6 h, washed with deionized water until neutral, and dried to obtain activated basalt fiber; (2) Silanization bridging modification: Prepare an ethanol / water (volume ratio 9:1) mixed solvent, add 1 wt% silane coupling agent KH-550 and stir evenly. Immerse the activated fiber obtained in step (1) into the solution, react at 60℃ for 6h, take it out and wash it thoroughly with deionized water and dry it to obtain amino-functionalized basalt fiber; (3) In-situ growth of cobalt-zinc bimetallic ZIF: Co(NO3)2·6H2O and Zn(NO3)2·6H2O were weighed according to the Co / Zn molar ratio of 1:2 and dissolved in deionized water to obtain a mixed metal salt solution; 2-methylimidazolium was dissolved in deionized water as a ligand solution, and the ratio of ligand to total metal salt was 6:1. The mixed metal salt solution was quickly poured into the ligand solution and stirred at room temperature for 10 min. Then, the amino-functionalized fiber obtained in step (2) was added, and the product was hydrothermally reacted at 45℃ for 12 h. The product was repeatedly washed with deionized water, dried, and then carbonized in a tube furnace. The temperature was increased to 700℃ at 5℃ / min under a nitrogen atmosphere and held for 0.5 h to obtain microwave absorbing basalt fiber.
[0037] (4) Figure 2 Figures b1-b3 show the SEM morphology of the fiber surface obtained in this embodiment. It can be seen that the ZIF-derived carbon on the fiber surface exhibits a sparse, needle-like morphology. Combined with subsequent microwave absorption performance tests, it is evident that the interfacial polarization and conductivity loss capabilities are weak under this morphology, and the microwave absorption performance needs improvement.
[0038] (5) Absorption performance test, such as Figure 4 As shown in Figure b, the minimum reflection loss at a thickness of 7.7 mm is -7.02 dB, indicating that effective absorption has not been achieved.
[0039] Example 3 The microwave-absorbing basalt fiber with cobalt-zinc bimetallic organic framework grown in situ on the surface of this embodiment and its preparation method specifically include the following steps: (1) Basalt fiber pretreatment: Basalt fiber was placed in nitric acid aqueous solution (H2O:HNO3 volume ratio 2:1), etched at 60℃ for 4 h, washed with deionized water until neutral, and dried to obtain activated basalt fiber; (2) Silanization bridging modification: Prepare an ethanol / water (volume ratio 9:1) mixed solvent, add 1 wt% silane coupling agent KH-550 and stir evenly. Immerse the activated fiber obtained in step (1) into the solution, react at 25℃ for 12h, take it out and wash it thoroughly with deionized water and dry it to obtain amino-functionalized basalt fiber; (3) In-situ growth of cobalt-zinc bimetallic ZIF: Co(NO3)2·6H2O and Zn(NO3)2·6H2O were weighed according to the Co / Zn molar ratio of 2:1 and dissolved in deionized water to obtain a mixed metal salt solution; 2-methylimidazolium was dissolved in deionized water as a ligand solution, and the ratio of ligand to total metal salt was 12:1. The mixed metal salt solution was quickly poured into the ligand solution and stirred at room temperature for 10 min. Then, the amino-functionalized fiber obtained in step (2) was added, and the product was hydrothermally reacted at 80℃ for 9 h. The product was repeatedly washed with deionized water, dried, and then carbonized in a tube furnace. The temperature was increased to 700℃ at 10 ℃ / min under a nitrogen atmosphere and held for 1 h to obtain microwave absorbing basalt fiber.
[0040] (4) Figure 2 Figures c1-c3 show the SEM morphology of the fiber surface obtained in this embodiment. It can be seen that the ZIF-derived carbon on the fiber surface exhibits a distinct petal-like morphology, which is assembled from stacked two-dimensional sheets. This structure is beneficial for increasing the interfacial contact area and the ability to dissipate electromagnetic waves through multiple reflections.
[0041] (5) Absorption performance test, such as Figure 4 As shown in Figure c, the minimum reflection loss reaches -46.98 dB at a thickness of 7.1 mm, with an effective absorption bandwidth of 4.16 GHz; the effective absorption bandwidth reaches 4.56 GHz at a thickness of 7.3 mm.
[0042] Example 4 The microwave-absorbing basalt fiber with cobalt-zinc bimetallic organic framework grown in situ on the surface of this embodiment and its preparation method specifically include the following steps: (1) Basalt fiber pretreatment: Basalt fiber was placed in nitric acid aqueous solution (H2O:HNO3 volume ratio 2:1), etched at 60℃ for 4 h, washed with deionized water until neutral, and dried to obtain activated basalt fiber; (2) Silanization bridging modification: Prepare an ethanol / water (volume ratio 9:1) mixed solvent, add 1 wt% silane coupling agent KH-550 and stir evenly. Immerse the activated fiber obtained in step (1) into the solution, react at 60℃ for 12h, take it out and wash it thoroughly with deionized water and dry it to obtain amino-functionalized basalt fiber; (3) In-situ growth of cobalt-zinc bimetallic ZIF: Co(NO3)2·6H2O and Zn(NO3)2·6H2O were weighed according to the Co / Zn molar ratio of 3:1 and dissolved in deionized water to obtain a mixed metal salt solution; 2-methylimidazolium was dissolved in deionized water as a ligand solution, and the ratio of ligand to total metal salt was 8:1. The mixed metal salt solution was quickly poured into the ligand solution and stirred at room temperature for 10 min. Then, the amino-functionalized fiber obtained in step (2) was added, and the product was hydrothermally reacted at 65℃ for 6 h. The product was repeatedly washed with deionized water, dried, and then carbonized in a tube furnace. The temperature was increased to 700℃ at 5℃ / min under a nitrogen atmosphere and held for 2 h to obtain microwave absorbing basalt fiber.
[0043] (4) Figure 2 Figures d1-d3 show the SEM morphology of the fiber surface obtained in this embodiment. It can be seen that the ZIF-derived carbon morphology has evolved into a uniform, fine granular packing with uniform particle size and dense distribution. This morphology is conducive to the formation of a three-dimensional conductive network, which significantly improves the dielectric loss capability.
[0044] (5) Absorption performance test, such as Figure 4 As shown in Figure d, the minimum reflection loss is -53.07 dB at a thickness of 2.7 mm and a frequency of 12.72 GHz, with an effective absorption bandwidth of 6.32 GHz; the effective absorption bandwidth reaches a maximum of 6.88 GHz at a thickness of 2.5 mm.
[0045] (6) To evaluate the stealth performance of the absorbing fiber of the present invention in practical application scenarios, based on the electromagnetic parameters of the fiber obtained in this embodiment, the radar cross section (RCS) of the perfectly conductive (PEC) plate before and after coating with the absorber was simulated and calculated in the incident angle range of -90° to 90°. The results are as follows: Figure 5 As shown. Figure 5 As shown, at a 0° incident angle, the RCS of the uncoated PEC plate is as high as 18.77 dB·m. 2 However, after coating the absorbing fiber prepared in Example 4, the RCS decreased to -14.4 dB·m. 2 The reduction exceeds 33 dB·m 2 Furthermore, it exhibits excellent RCS reduction within the range of -90° to 90°. This result fully demonstrates that the radar-absorbing basalt fiber prepared in this invention also has great application potential in practical radar stealth applications.
[0046] Comparative Example 1 The difference from Example 1 is that the etching time in step (1) is 2 hours, while the remaining steps and process parameters are the same as in Example 1. The results are as follows: Figure 6As shown in (a), the ZIF loading on the fiber surface is low and extremely uneven. The reason for this is that insufficient etching time results in insufficient fiber surface roughness, a lack of effective anchoring points, and difficulty in the dense nucleation and growth of ZIF crystals on the fiber surface. This comparative example shows that an excessively short etching time cannot provide sufficient surface conditions for the subsequent uniform loading of ZIF.
[0047] Comparative Example 2 The difference from Example 1 is that the etching time in step (1) is 8 hours, while the remaining steps and process parameters are the same as in Example 1.
[0048] The results are as follows Figure 6 As shown in (b), obvious pitting and peeling phenomena appear on the fiber surface, indicating irreversible damage to the intrinsic structure. Although the ZIF has a certain load in the damaged area, the destruction of the fiber's mechanical integrity renders it unusable as a structural skeleton. This comparative example shows that excessive etching will damage the fiber's intrinsic structure, and the etching time must be controlled within a reasonable range.
[0049] Comparative Example 3 The difference from Example 1 is that the silanization modification treatment in step (2) is omitted. The basalt fibers etched in step (1) are directly immersed in the ZIF growth solution to carry out the reaction in step (3). The remaining steps and process parameters are the same as in Example 1.
[0050] The results are as follows Figure 7 As shown, the ZIF particle loading on the fiber surface is relatively low, and the multi-level rough heterogeneous interface structure constructed by ZIF crystals, as seen in Examples 1-4, is not exhibited. The reason for this is that the fiber surface without silane coupling agent modification lacks active anchoring sites such as amino groups, altering the ZIF nucleation density and crystal growth orientation. The crystals tend to grow freely and deposit as dense planes, rather than constructing a heterogeneous structure with high specific surface area and multi-level roughness in situ on the fiber surface. This comparative example confirms the necessity of silanization bridging modification for inducing the formation of multi-level ZIF heterogeneous structures on the basalt fiber surface.
[0051] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.
Claims
1. A method for preparing microwave-absorbing basalt fibers with in-situ grown cobalt-zinc bimetallic organic frameworks, characterized in that, Includes the following steps: S1. Basalt fiber pretreatment: Basalt fibers are immersed in nitric acid etching solution to perform surface roughening etching treatment, thereby obtaining activated basalt fibers. S2. Fiber surface silanization modification: The activated basalt fiber obtained in S1 is immersed in a solution containing KH550 silane coupling agent to carry out silanization grafting modification to obtain amino-functionalized basalt fiber. S3. In-situ growth of Co-Zn bimetallic organic framework: Cobalt and zinc salts are dissolved in deionized water to prepare a mixed metal salt solution. 2-Methylimidazole is dissolved in deionized water to form a ligand solution. The mixed metal salt solution is added to the ligand solution and stirred to obtain a mixed solution. The amino-functionalized basalt fibers obtained in S2 are immersed in the mixed solution and subjected to a hydrothermal synthesis reaction. After filtration and washing, the product is subjected to carbonization treatment to obtain microwave absorbing basalt fibers with in-situ grown cobalt-zinc bimetallic organic framework.
2. The method for preparing microwave-absorbing basalt fibers with in-situ surface-grown cobalt-zinc bimetallic organic frameworks according to claim 1, characterized in that, The surface roughening etching process in S1 is carried out at a temperature of 40~60℃ for a time of 4~6h.
3. The method for preparing microwave-absorbing basalt fibers with in-situ surface-grown cobalt-zinc bimetallic organic frameworks according to claim 1, characterized in that, The silanization grafting modification process in S2 takes 6-12 hours and is carried out at a temperature of 25°C-60°C.
4. The method for preparing microwave-absorbing basalt fibers with in-situ surface-grown cobalt-zinc bimetallic organic frameworks according to claim 1, characterized in that, The molar ratio of cobalt metal to zinc metal in S3 is 1:2 to 3:
1.
5. The method for preparing microwave-absorbing basalt fibers with in-situ surface-grown cobalt-zinc bimetallic organic frameworks according to claim 4, characterized in that, The molar ratio of 2-methylimidazole to the total amount of cobalt and zinc metals in S3 is 6:1 to 12:
1.
6. The method for preparing microwave-absorbing basalt fibers with in-situ surface-grown cobalt-zinc bimetallic organic frameworks according to claim 1, characterized in that, The hydrothermal synthesis reaction in S3 is carried out at a temperature of 45~80℃ for 6~12h.
7. The method for preparing microwave-absorbing basalt fibers with in-situ surface-grown cobalt-zinc bimetallic organic frameworks according to claim 1, characterized in that, The carbonization process in S3 specifically involves heating to 700°C at a rate of 5-10°C / min, followed by a heat preservation treatment for 0.5-2 hours.
8. A microwave-absorbing basalt fiber with a cobalt-zinc bimetallic organic framework grown in situ on its surface, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
9. The microwave absorbing basalt fiber with a cobalt-zinc bimetallic organic framework grown in situ on the surface according to claim 8, characterized in that, The absorbing basalt fiber with a cobalt-zinc bimetallic organic framework grown in situ on the surface has a minimum reflection loss of -7.02 dB to -53.07 dB and an effective absorption bandwidth of 0 to 6.88 GHz.
10. The application of the surface-grown cobalt-zinc bimetallic organic framework absorbing basalt fiber as described in claim 8 as an electromagnetic wave absorber in resin-based, coating-based, or paper-based composite materials.